2010
DOI: 10.1002/jcop.20393
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perceived neighborhood safety on proactive and reactive aggression

Abstract: The current study examined associations between perceived neighborhood safety and proactive and reactive subtypes of aggression while also considering peer delinquency and poor parental monitoring in a community recruited sample of 89 children (56% male) ranging from 9 to 12 years of age (M=10.44, SD=1.14). In addition, neighborhood safety was examined as a moderator of the associations between peer delinquency and poor parental monitoring and proactive and reactive aggression. Findings suggested that while pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…Second we hypothesized that while reactive aggression is positively associated with trait anger, anxiety, depression and hostility, proactive aggression is not as consistent with earlier studies (Card and Little, 2006;Raine et al, 2006;Fite et al, 2009;Vitaro et al, 2002). Third, we hypothesized that subscales of RPQ are positively associated with delinquent behaviors (Card and Little, 2006), deviant peers (Fite et al, 2010) and attitudes towards violence. Fourth, we hypothesized that males would score higher than females, both in the reactive and proactive forms of aggression (Salmivalli and Nieminen, 2002).…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Second we hypothesized that while reactive aggression is positively associated with trait anger, anxiety, depression and hostility, proactive aggression is not as consistent with earlier studies (Card and Little, 2006;Raine et al, 2006;Fite et al, 2009;Vitaro et al, 2002). Third, we hypothesized that subscales of RPQ are positively associated with delinquent behaviors (Card and Little, 2006), deviant peers (Fite et al, 2010) and attitudes towards violence. Fourth, we hypothesized that males would score higher than females, both in the reactive and proactive forms of aggression (Salmivalli and Nieminen, 2002).…”
Section: Introductionmentioning
confidence: 64%
“…Laird et al (1999) determined that those who define their best friends as those with high antisocial behaviors define themselves in a similar way. Some researchers indicated that peer guilt is associated with aggression Fite et al 2010). Fite et al (2010) reported that peer guilt is correlated with both reactive and proactive aggression, but has a stronger relationship with reactive aggression than proactive aggression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations